Mesin Pengolahan Sampah Plastik Menjadi Pelet Plastik - Pratama, Rio Wicandaru, Hasyim Asy'ari, ST.MT (2017)
Plastic waste is one of the very difficult issues in people's lives. this is because the plastic waste can not be decomposed by bacteria or included in the inorganic waste. The high plastic waste in Indonesia would cause problems if not to take seriously. In this case the required awareness of the public to be able to process plastic waste into useful things. The purpose of this research is to design and make the machine processing plastic waste into plastic pellets. The method used is the manufacture of plastic waste processing machine and the installation of components such as heating elements, plugs, tube containers. How to observations made are related to how data retrieval Kg plastic waste that can be melted down for hourly and KWh generated during testing. The experimental results weighing 1.25 Kg plastic waste takes three hours to convert the plastic into pellets with the engine load of 400 watts. Changes in weight of the plastic that had melted into pellets is 0.88 kg with the conversion gains achieved by the use of power is as follows: 450VA power = Rp. 4750, power 900 VA = Rp. 3813, and 1300 VA power = Rp. 3697, of the results can be known that with the power of 450 VA, the benefits to be gained will be higher.